Mast cells are directly activated by contact with cancer cells by a mechanism involving autocrine formation of adenosine and autocrine/paracrine signaling of the adenosine A3 receptor. (1st July 2017) - Gorzalczany, Yaara; Akiva, Eyal; Klein, Ofir; Merimsky, Ofer; Sagi-Eisenberg, Ronit
Abstract: Mast cells (MCs) constitute an important part of the tumor microenvironment (TME). However, their underlying mechanisms of activation within the TME remain poorly understood. Here we show that recapitulating cell-to-cell contact interactions by exposing MCs to membranes derived from a number of cancer cell types, results in MC activation, evident by the increased phosphorylation of the ERK1/2 MAP kinases and Akt, in a phosphatidylinositol 3-kinase dependent fashion. Activation is unidirectional since MC derived membranes do not activate cancer cells. Stimulated ERK1/2 phosphorylation is strictly dependent on the ecto enzyme CD73 that mediates autocrine formation of adenosine, and is inhibited by knockdown of the A3 adenosine receptor (A3R) as well as by an A3R antagonist or by agonist-stimulated down-regulation of the A3R. We also show that cancer cell mediated triggering upregulates expression and stimulates secretion of interleukin 8 from the activated MCs. These findings provide evidence for a novel mode of unidirectional crosstalk between MCs and cancer cells implicating direct activation by cancer cells in MC reprogramming into a pro tumorigenic profile. Highlights: Mast cells are activated by membranes derived from cancer cells, conditions that recapitulate cell-to-cell contact. Mast cell activation by pancreatic cancer cell derived membranes involves activation of PI3K, Akt and the ERK1/2 MAP kinases. Mast cell activation by pancreatic cancer cell derived membranes involves autocrine signaling of adenosine. Mast cell activation by pancreatic cancer cell derived membranes is partially mediated by the A3 adenosine receptor. Mast cell activation by pancreatic cancer cell derived membranes results in upregulation and release of IL8.